An international study of carbon information asymmetry and independent carbon assurance. Issue 1 (January 2021) - Fan, Hanlu; Tang, Qingliang; Pan, Lipeng
Abstract: Protecting the environment is now a major aspect of corporate social responsibility. However, voluntary carbon disclosure includes private information on future sustainability that external stakeholders cannot easily verify. Drawing on information asymmetry theory, we predict that companies with higher carbon information asymmetry between insiders and outsiders have a greater incentive to voluntarily engage an external party for the independent assurance of their greenhouse gas statements. Using data from the CDP, we test this hypothesis and find that our proxies for carbon information asymmetry (e.g., greenhouse gas emissions, energy structure) are significantly associated with the adoption of carbon assurance. Further analyses suggest that the probability of carbon assurance is enhanced when carbon disclosure is inadequate to diminish information asymmetry. Finally, our sample companies adopted carbon assurance in addition to financial auditing. This highlights the key point that resolving carbon information asymmetry requires carbon assurance, which cannot be substituted for by financial auditing.